2018
DOI: 10.12659/msm.903243
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Medical Ozone on Lumbar Disc Herniation

Abstract: BackgroundThis study aimed to investigate the therapeutic effect of low, medium, and high concentrations of medical ozone on trauma-induced lumbar disc herniation.Material/MethodsA total of 80 patients were included and were grouped into a control group, a low medical ozone (20 μg/ml) group, a medium medical ozone (40 μg/ml) group, and a high medical ozone (60 μg/ml) group. The CT scan and enzyme-linked immunosorbent assay (ELISA) were used to detect IL-6 level, SOD activity, IgM, and IgG levels upon admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
0
28
0
3
Order By: Relevance
“…1 In a randomized trial conducted by Niu et al investigating the therapeutic effect of low, medium and high concentrations of medical ozone on patients with trauma-induced lumbar disc herniation, the group receiving a medium volume of medical ozone (40 mg/ml) showed the greatest disc retraction rate. 7 Muto et al conducted oxygen-ozone chemonucleolysis procedures in 2900 patients with lumbar disc herniation and reported success rates of 75-80% for soft disc herniation, 70% for multiple disc herniation and 55% for failed back surgery syndrome. 8 Paoloni et al in a multicenter randomized, double-blind, therapy-controlled trial among patients with acute low back pain due to lumbar disc herniation found that patients who received ozone therapy had significantly lower mean pain scores than patients who received simulated therapy throughout the observation period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In a randomized trial conducted by Niu et al investigating the therapeutic effect of low, medium and high concentrations of medical ozone on patients with trauma-induced lumbar disc herniation, the group receiving a medium volume of medical ozone (40 mg/ml) showed the greatest disc retraction rate. 7 Muto et al conducted oxygen-ozone chemonucleolysis procedures in 2900 patients with lumbar disc herniation and reported success rates of 75-80% for soft disc herniation, 70% for multiple disc herniation and 55% for failed back surgery syndrome. 8 Paoloni et al in a multicenter randomized, double-blind, therapy-controlled trial among patients with acute low back pain due to lumbar disc herniation found that patients who received ozone therapy had significantly lower mean pain scores than patients who received simulated therapy throughout the observation period.…”
Section: Introductionmentioning
confidence: 99%
“…investigating the therapeutic effect of low, medium and high concentrations of medical ozone on patients with trauma-induced lumbar disc herniation, the group receiving a medium volume of medical ozone (40 µg/ml) showed the greatest disc retraction rate. 7 Muto et al. conducted oxygen-ozone chemonucleolysis procedures in 2900 patients with lumbar disc herniation and reported success rates of 75–80% for soft disc herniation, 70% for multiple disc herniation and 55% for failed back surgery syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration for ozone ablation in the treatment of herniated lumbar intervertebral disc is usually 40 μg/mL[ 46 , 47 ]. The capacity of each lumbar spine disc is 4-5 mL[ 46 ], and the capacity of each cervical spine disc is 2-3 mL. The injection rate should be slow, and the patient’s response should be observed throughout.…”
Section: Ozone Injection Ablation For the Treatment Of Intervertebralmentioning
confidence: 99%
“…In local injection, such as intradiscal injection, used mainly for back pain such as disc herniation, an average of 50 µg/mL of ozone is usually injected into an ozone/oxygen mixture (Niu et al, 2018). Also, there are intrapatellar ozone injection protocols at an average concentration of 15 µg/mL that is effective in treating osteoarthritis (Babaei-Ghazani et al, 2018).…”
Section: Safety Dose and Clinical Protocolmentioning
confidence: 99%